Perspective : an action plan for future management of Canada goose populations in east-central Wisconsin - U.S. Fish and Wildlife Service.; Wisconsin. Dept. of Natural Resources. ([Washington] : The Service, 1976)
"First Edition April 1976" Cover title. Mode of access: Internet.